Oxygen plasma treatments of polydimethylsiloxane surfaces: effect of the atomic oxygen on capillary flow in the microchannels. (1st October 2017) - Ruben, Bartali; Elisa, Morganti; Leandro, Lorenzelli; Victor, Micheli; Gloria, Gottardi; Marina, Scarpa; Mian K, Safeen; Pandiyan, Rajesh; Nadhira, Laidani
Abstract : Modification of polydimethylsoloxane/water interaction, to promote a spontaneous water flux through the microchannels, is a crucial task in microfluidic applications. For that reason, in this research, the authors study the hydrophilicity improvement induced by low‐power oxygen plasma treatments (15 W) on the polydimethylsiloxane (PDMS) microchannel. The effects of the oxygen plasma treatments on wettability and water‐work of adhesion on PDMS surfaces have been studied by sessile contact angle. The chemical composition of the plasma has been investigated by means of optical emission spectroscopy. The results indicate that the improvement of wettability on treated PDMS is led by the percentage of atomic oxygen in the plasma discharge. Super‐hydrophilic surfaces (contact angle < 5°) have been obtained optimising the atomic oxygen percentage in the plasma discharge varying only the plasma working pressure. Super‐hydrophilic PDMS microchannels show the highest spontaneous capillary flow in the channels while the hydrophilic microchannel shows only a small capillary flow.